Study of structural and optical properties of CaMoO4 ceramic synthesized by solid state reaction route. (10th September 2017) - Sinha, E.; Yadav, P.
ABSTRACT: Scheelite-type calcium molybdate (CaMoO4 ) was synthesized by conventional solid state reaction route. X-ray diffraction pattern confirmed the formation of monophasic tetragonal CaMoO4 . The shape, growth and average crystal size distribution of this crystal was investigated by SEM technique. FT-Raman spectra exhibited 10 different Raman active vibrational modes in the range from 100 to 1000 cm −1 . FT-IR spectra exhibited a large absorption band which is associated to the Mo–O anti-symmetric stretching vibrations of the [MoO4 ] cluster. UV-Vis absorption spectra revealed the involvement of direct band gap and emission spectra towards green region of the visible spectra.